PASAR SUKUK: SISTEM DAN OPERASIONALNYA DI INDONESIA - Rachma Febriyanti; Tacong, Hamzah; Lutfi, Mukhtar; Kadir, Amiruddin (LPPM STAI Muhammadiyah Probolinggo, 2026)
Sukuk has become a strategic instrument in global Islamic finance and an important pillar of development financing in Indonesia, especially after the enactment of the Sovereign Sukuk Law (SBSN) in 2008. However, the rapid expansion of sovereign sukuk has not been matched by adequate public understanding or corporate participation, reflecting the need for a clearer examination of sukuk concepts, systems, and operations. This study employs a qualitative approach through a literature review of regulations, DSN-MUI fatwas, and reports from OJK, BI, and KNEKS, supported by academic publications. Using a descriptive–analytical method, the study explores the structure, mechanisms, challenges, and prospects of the sukuk market in Indonesia. The findings indicate that sukuk is based on real ownership, the prohibition of riba, and Sharia-compliant contracts, distinguishing it from conventional bonds. Indonesia’s sukuk market operates within a strong regulatory framework, with issuance involving contract structuring, underlying asset determination, and primary and secondary market processes. Despite significant growth, challenges remain, including low literacy, limited Sharia infrastructure, and modest corporate sukuk issuance. Nonetheless, regulatory support, digitalization through e-SBN, and rising interest in sustainable instruments highlight sukuk’s potential to strengthen development financing and deepen the Islamic financial market.